EFEKTIVITAS AROMATERAPI (LAVANDULA ANGUSTIFOLIA) DALAM PELAYANAN HOMECARE TERHADAP PENURUNAN GEJALA BABY BLUES PADA IBU NIFAS - Rika Armalini; Resi Citra M (Akademi Kebidanan Harapan Bunda Bima, 2026)
Baby blues is a mild psychological disorder commonly experienced by postpartum mothers during the first to second week after childbirth, characterized by feelings of sadness, frequent crying, anxiety, mood swings, fatigue, and sleep disturbances. This condition may affect the mother’s quality of life, mother-infant bonding process, and newborn care success. One of the non-pharmacological interventions that can be used to reduce baby blues symptoms is lavender aromatherapy (Lavandula angustifolia), which has relaxation, anxiolytic, and sleep-enhancing effects. This study aimed to determine the effectiveness of lavender aromatherapy in homecare services on reducing baby blues symptoms among postpartum mothers in the working area of Pariaman Public Health Center in 2026. This study used a pre-experimental design with a one-group pretest-posttest design approach. The population in this study consisted of all postpartum mothers experiencing baby blues symptoms in the working area of Pariaman Public Health Center in 2026. The sampling technique used was purposive sampling with a total sample of 20 respondents. Baby blues symptoms were measured using the Edinburgh Postnatal Depression Scale (EPDS) questionnaire before and after the administration of lavender aromatherapy intervention in homecare services for 7 days. Data were analyzed using the Wilcoxon Signed Rank Test. The results showed a decrease in baby blues symptom scores among postpartum mothers after receiving lavender aromatherapy in homecare services, with a mean score before intervention of 15.20 and after intervention of 8.45. Statistical test results showed a p-value = 0.001 (<0.05), indicating that lavender aromatherapy was effective in reducing baby blues symptoms among postpartum mothers. In conclusion, lavender aromatherapy is effective in reducing baby blues symptoms among postpartum mothers and can be used as a complementary intervention in nursing homecare services to improve postpartum maternal mental health.